A law of the Integrated Logarithm for the Tail Sums of Dyadic Martingales Using Stopping Times - Acharya, Ananta; Ghimire, Santosh (Journal of Advanced College of Engineering and Management, 2016)
Stopping times have been used in number of places in the derivation of law of iterated logarithm for various contexts. In this article, we obtain a law of the iterated logarithm for the tail sums of dyadic martingales using stopping times. Journal of Advanced College of Engineering and Management, Vol. 2, 2016, page: 79-83